Development of Tarkib Teaching Materials Based on Motion Graphic in Islamic Junior High School l Tatwir al-Mawad al-Tarkibiyyah ‘ala Asas al-Rasum al-Mutakharrikah bi al-Madrasah al-Mutawassitah al-Islamiyyah - Nufus, Hayati; Erlina, Erlina; Koderi, Koderi; Ramadhan, Mahendra Utama Cahya; Nopiyanti, Nopiyanti (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
This research was based on the problems about teaching materials which was less attractive because the teaching materials were initially not based on technology. The aims of this study was to develop tarkib teaching materials based on motion graphic for 7th graders of Islamic junior high school by analyzing the necessity and the feasibility of tarkib teaching materials based on motion graphic according to the experts’ assessment. This research data were obtained from interviews and students’ responses to teaching materials. The interviews were conducted with groups of students as participants in the research. Meanwhile, the students’ responses were confirmed to 34 students. Thus, the results of this research were as follows: 1) Tarkib teaching materials in the form of print out and video based on motion graphic. 2) The products were very feasible, 93% according to design experts, 93% to material experts, 90% to media experts. 3) The results of the product effectiveness trial of  tarkib teaching materials based on motion graphic were 90% for one to one learner, 95% for the small group test. The development of tarkib teaching materials based on motion graphic had a significant effect on the Arabic teaching materials especially tarkib and could make students more active, independent and comfortable during the learning process. Hence, this paper suggested the teacher and institution in solving the problems in Arabic learning especially tarkib.